Differential 1‐year clinical outcomes for ST‐segment elevation myocardial infarction related to stent thrombosis or saphenous vein graft thrombosis. Issue 2 (7th May 2013) - Arzamendi, Dabit; Ly, Hung Q.; Tanguay, Jean‐François; Armero, Sebastien; Jilaihawi, Hasan; Gallo, Richard; Ibrahim, Reda; L'Allier, Philippe; Blondeau, Lucie; Gosselin, Gilbert; Gregoire, Jean; Doucet, Serge
<x xml:space="preserve">Abstract</x> Aim: Thrombosis of stents and of saphenous vein grafts (SVG) remains a severe complication of either revascularization techniques that often are present as ST elevation myocardial infarction (STEMI). The aim of this longitudinal cohort study was to compare the 1‐year clinical outcomes among STEMI patients requiring primary PCI due to stent thrombosis and graft occlusion presenting with STEMI. Methods and Results: We prospectively collected data on all patients undergoing primary PCI at the Montreal Heart Institute between April 1, 2007 and March 30, 2008. Study patients were grouped according to the etiology of the STEMI: stent thrombosis, graft thrombosis, or atherosclerosis‐related STEMIs (control group). The primary combined end‐point, major adverse cardiac events (MACE), was defined as death, myocardial infarction, and target vessel revascularization within 12 months as primary end point. Of the 489 STEMI patients included in the study, 23 were due to stent thrombosis, 22 to graft thrombosis, and 444 in the control group. Stent and graft thromboses were associated with a higher MACE rates, 26.1 and 22.7%, respectively, compared to the control group, 9.3% (P = 0.004). Moreover, only stent thrombosis was associated with an increased risk of MACE (HR 2.57, confidence interval 95% 1.08–6.08. Conclusion: Patients with stent thrombosis present with higher rate of reinfarction while graft thrombosis is associated with an increase in 1‐year cardiac mortality. Using multivariate analysis, higher MACE rates were associated with stent thrombosis as compared to graft thrombosis. © 2013 Wiley Periodicals, Inc.